Implementing Wordwall in Teaching Sampling Techniques for Higher Education Students - Listiani, Tanti (KnE Social Sciences, 2024)
This research aimed to determine the use of the Wordwall in online learning on sampling techniques material for higher education students. The use of this application was reviewed through test results and questionnaires. This research used combination research by combining quantitative and qualitative data collection techniques. The subjects of this research were 53 students from Teachers College in Universitas Pelita Harapan (UPH) that took Statistics for Educational Research course. The result displayed that the quizzes given on Wordwall can help students to learn about sampling techniques and materials with positive responses. Good feedback from students showed that they felt happy in doing the learning activity on Wordwall. There were almost 90% of students who said that they enjoyed the learning. In the end, Wordwall is recommended to be implemented in higher education classrooms. Keywords: higher education students, teaching sampling techniques, wordwall